Adhesion of nc lacquer on 3 different sanded surfaces of Kelempayan timber / Radhiah Abd Aziz - Abd Aziz, Radhiah (Faculty Of Applied Sciences, 2015)
This research project was carried out to determine the adhesion lacquer on sanded surface of timber. Kelempayan timber was used for this purpose. 3 types of grit of sand paper had been use. Timber prepared to moisture content 12%. Cross cut test were applied based ASTM D3359 09'2. Result show that 80 grit size gave better result. It is significant different. It can be concluded rough surface better adhesion.